2017
DOI: 10.18203/2319-2003.ijbcp20175683
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, perceptions and assessment of effectiveness of educational intervention on Pharmacovigilance among undergraduate medical students at Gulbarga Institute of Medical Sciences, Kalaburagi, India

Abstract: Background: The Study was designed to assess the awareness of Pharmacovigilance and to evaluate the impact of an educational intervention.Methods: This was a questionnaire-based pre- and post-test educational interventional study. Students were given handouts containing information about pharmacovigilance one month before the educational intervention. A pre-validated 20-point questionnaire on (KAP) Knowledge, attitude, perception about Pharmacovigilance was distributed to second year medical students (n=115). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…[ 8 14 ] In one study by Harish G. Bagewadi, there was a significant improvement regarding awareness about healthcare professionals reporting ADR after educational intervention. [ 11 ] Preintervention, majority of the respondents were of the opinion that ADR reporting has to be done only for allopathic medicines which is similar to the findings reported by Gupta and Udupa. [ 8 ] This concept of the respondents changed after the educational intervention.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…[ 8 14 ] In one study by Harish G. Bagewadi, there was a significant improvement regarding awareness about healthcare professionals reporting ADR after educational intervention. [ 11 ] Preintervention, majority of the respondents were of the opinion that ADR reporting has to be done only for allopathic medicines which is similar to the findings reported by Gupta and Udupa. [ 8 ] This concept of the respondents changed after the educational intervention.…”
Section: Discussionsupporting
confidence: 71%
“…Very few studies are there to assess the knowledge, attitude of PV among undergraduate medical students, and these studies indicate inadequate knowledge about PV among health-care professionals. In one study,[ 11 ] interactive educational intervention on PV among undergraduate medical students was found to be effective. However, the results of these studies cannot be applied to medical students in our institute as KAP among the students will differ from institute to institute.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study reports a significant improvement in reporting ADR by healthcare professionals after educational intervention. [ 15 ] Regular awareness programs are the best platforms for the Ayurveda fraternities who are in the field of teaching and clinical practice to preserve their competence and acquire newer developments in their respective field. Further, the awareness can also be developed, among various stake holders, considering their in the form of circulations of written periodicals, newsletter, audio, video, or other forms of electronic media and conducting various competitions like essay, debate etc.…”
Section: Resultsmentioning
confidence: 99%
“…The limited information regarding the location of the present national pharmacovigilance co-ordinating centre, the official website of the pharmacovigilance program can be attributed to restricted information regarding recent advances and updates of pharmacovigilance in the present curriculum. This lacuna can be improved by educational interventions as reports from the published study also reveals a significant improvement in reporting ADR by healthcare professionals after educational intervention (Bagewadi et al, 2018). Available literature also shows that interactive educational intervention on PV among undergraduate medical students and healthcare professionals (Bagewadi et al, 2018;Rajesh et al, 2011) were found to be effective in increasing awareness.…”
Section: Discussionmentioning
confidence: 93%
“…This lacuna can be improved by educational interventions as reports from the published study also reveals a significant improvement in reporting ADR by healthcare professionals after educational intervention (Bagewadi et al, 2018). Available literature also shows that interactive educational intervention on PV among undergraduate medical students and healthcare professionals (Bagewadi et al, 2018;Rajesh et al, 2011) were found to be effective in increasing awareness. However, some studies conclude that only knowledge does not help in increased ADR reporting.…”
Section: Discussionmentioning
confidence: 93%